2015
DOI: 10.1103/physrevb.92.104514
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signatures of topological transitions for interacting fermions in chain lattices

Abstract: We study one-component fermions in chain lattices with proximity-induced superconducting gap and interparticle short-range interaction, capable of hosting Majorana fermions. By systematically tracking various physical quantities, we show that topological states and topological phase transitions in the system can be identified by multiple signatures in thermodynamic quantities and pair-condensate properties, in good agreement with the known signatures in the ground-state energy and entanglement spectrum. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 119 publications
3
38
0
1
Order By: Relevance
“…2(b)], thus rendering the criterion unreliable. A related criterion, namely the compressibility −∂ 2 E GS /∂μ 2 , was discussed recently [29] and shown to be insensitive to finite-size effects. However, in the disordered case the compressibility shows the same problems as the energy gap.…”
Section: Possible Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…2(b)], thus rendering the criterion unreliable. A related criterion, namely the compressibility −∂ 2 E GS /∂μ 2 , was discussed recently [29] and shown to be insensitive to finite-size effects. However, in the disordered case the compressibility shows the same problems as the energy gap.…”
Section: Possible Criteriamentioning
confidence: 99%
“…Two of the most relevant experimental influences are disorder [10][11][12][13][14][15][16][17] and interactions [11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Concerning the effects of disorder, it has been observed that moderate disorder supports the topological phase by pinning down quasiparticles associated with the phase transition, which has been investigated in particular for the two-dimensional toric code [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, considerable progress has been made towards developing number preserving theories of the Majorana modes, [15][16][17][18][19][20] as well as a growing body of work which examines how free-topological superconducting phases are affected by the addition of interacting electron-electron terms. [21][22][23][24][25][26][27][28][29][30][31][32][33] One aspect of this latter story is concerned with the stability and structure of the Majorana zero-modes themselves and how they are affected by the presence of density-density interaction terms that break the exactly solvable nature of the underlying model. The issue of stable zero-modes has also been addressed in the related context of 1-d parafermionic chains.…”
Section: Introductionmentioning
confidence: 99%
“…Majorana zero modes have attracted intensive studies in past years [1][2][3][4][5] . This is not only due to their potential applications in topological quantum computation 6 , but also some reported experimental evidences of their existence [7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%